Dinamika Program Penataan dan Pembangunan Kota Pusaka Lasem - Muhammad Taufany Rachman Eriz (Umbara, 2023)
This study  describes the dynamics of the revitalization and development of the historic city (Program Penataan dan Pembangunan Kota Pusaka) in Lasem District, Rembang Regency, Central Java. This program  has been carried out by the ministry of public works and housing to revitalize historic areas in Indonesia The  implementation of the program has brought some social dynamics and controversy in particular related to the impact of the program to the deterioration of the cultural heritage This study aims to demonstrate how various buildings and structures of the cultural heritage, as part of non-human actors, also play a significant role in social dynamics. This ethnographic study uses Charles Sanders Peirce's semiotic approach to explore various signs from various human and non-human actors in social reality. The findings of this study show that the  non-human actors have an essential role in the social dynamics and meaning making of the Heritage City Planning and Development Program. In particular, it has a significant role to affect and being affected by human action.